1998
DOI: 10.4269/ajtmh.1998.59.426
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leishmanial IgE antibodies: a marker of active disease in visceral leishmaniasis.

Abstract: Abstract. Visceral leishmaniasis (VL) is characterized by a depression of the T helper cell type 1 immune response. Although mRNA expression for interleukin-4 (IL-4) is observed, evidence of the role of this cytokine in the pathogenesis of VL has been lacking. Since IL-4 is involved in IgE synthesis, we measured the total IgE and Leishmania antigen-specific IgE antibody levels in sera from patients with VL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
1
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 35 publications
1
32
1
5
Order By: Relevance
“…The recent studies on the dichotomy of immune response in Th1 and Th2 (Coffman et al 1991), which is related to the pattern of cytokines produced during antigenic stimulation, have shown that IgE is the mainly antibody induced by IL-4 and IL-13 during a Th2 immunologic event (Romagnani 1998, 2000, Hunter & Reiner 2000. This fact has provoked the interest in the research of this isotype of immunoglobulin in several diseases associated to a Th2 immunological pattern such as systemic lupus erythematosus and viral and parasitic infections (Elkayam et al 1995, Mazza et al 1995, Atta et al 1998. A common pitfall in serum IgE immunoassays to diagnosis infections by protozoa or helminth, also present in IgM tests, corresponds to false negative results originated by serologic competition of IgG antibodies, generally present in greater concentration, and affinity for common epitopes on target antigens.…”
mentioning
confidence: 99%
“…The recent studies on the dichotomy of immune response in Th1 and Th2 (Coffman et al 1991), which is related to the pattern of cytokines produced during antigenic stimulation, have shown that IgE is the mainly antibody induced by IL-4 and IL-13 during a Th2 immunologic event (Romagnani 1998, 2000, Hunter & Reiner 2000. This fact has provoked the interest in the research of this isotype of immunoglobulin in several diseases associated to a Th2 immunological pattern such as systemic lupus erythematosus and viral and parasitic infections (Elkayam et al 1995, Mazza et al 1995, Atta et al 1998. A common pitfall in serum IgE immunoassays to diagnosis infections by protozoa or helminth, also present in IgM tests, corresponds to false negative results originated by serologic competition of IgG antibodies, generally present in greater concentration, and affinity for common epitopes on target antigens.…”
mentioning
confidence: 99%
“…It is therefore difficult to differentiate a positive test result for suspected PKDL from a previous case of VL, limiting the value of these methods in areas of endemicity. Recent studies investigating the pathogenic significance of leishmanial antigen (LAg)-specific Ig isotypes and IgG subclasses have revealed variations in the diagnostic sensitivities and specificities of these antibodies in the sera of patients with kala-azar (2,4,6,43). The levels of these isotypes are significantly elevated during disease and undergo a differential decline following resolution of the infection (3,4,6).…”
mentioning
confidence: 99%
“…However, we verified in this study that IgE antileishmanial antibodies reacting strongly and specifically with glycosylated epitopes of L. chagasi promastigote are not detected in sera from healthy individuals from both leishmaniasis endemic and non-endemic areas. We already demonstrated that subjects presenting respiratory allergy do not react in antileishmanial IgE immunoassays (Atta et al 1998). Additionally, we also verified that glycosylated epitopes of horseradish peroxidase bearing alpha (1,3)-fucose and beta (1,2)-xylose are not recognized by antileishmanial IgE antibodies in immunoassays using this enzyme as antigen (data not shown).…”
Section: Discussionmentioning
confidence: 52%
“…Previously others and we observed that both antileishmanial IgG and IgE antibodies could be detected simultaneously in VL patients (Atta et al 1998, Anam et al 1999, the titers of these antibodies decreasing after cure. Such decrease of antibody titers was also documented in a following-up study of Indian VL patients (Kumar et al 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation